2018
DOI: 10.1177/0891243218759006
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Motherhood: Variations of Maternal Identities among Women in the Illegal Drug Economy

Abstract: this study examines negotiations of motherhood among women in the illegal hard drug economy in norway. Based on interviews with mothers who are users and dealers, this study analyzes four predominant maternal identities: grieving mothers, detached mothers, motherly dealers, and working mothers. Particularly relevant factors explaining variations in maternal identities include the timing of pregnancy, time spent with children, control over drug use, and place in the drug market hierarchy. By revealing patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Women also tended to speak more extensively about their children. The emphasis on children in the interviews with women probably reflects the importance of motherhood for women, including or maybe especially, for marginalized women (Grundetjern, 2018). It is also possible that this was influenced by gender dynamics in the interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Women also tended to speak more extensively about their children. The emphasis on children in the interviews with women probably reflects the importance of motherhood for women, including or maybe especially, for marginalized women (Grundetjern, 2018). It is also possible that this was influenced by gender dynamics in the interviews.…”
Section: Discussionmentioning
confidence: 99%
“…The high number of men not mentioning whether they had children was a striking finding. In comparison, all women dealers in the larger sample provided information about whether they had chil dren on their own initiative, and they brought up their children as a topic early in the interviews (see Grundetjern, 2018). This likely reflects gendered expectations of par enthood where the women felt obligated to account for their parental status, whereas the men did not.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we examine paternal identities among a group of marginalized fathers in Norway, all of whom used and dealt drugs. Whereas multiple studies have shown how drugusing mothers negotiate motherhood (for example, Baker and Carson, 1999;Grundetjern, 2018;Hardesty and Black, 1999), we know significantly less about how men who are involved in crime and drug use construct fatherhood (but see Magnus and Benoit, 2017;Moloney et al, 2009;Wilkinson et al, 2009). The tendency to focus on mothers rather than on fathers reflects a broader social pattern: the links between socie ty's expectations of fatherhood and masculinity are significantly weaker and the cultural content ascribed to fatherhood remains less clear than it is for motherhood (Gillis, 2000).…”
mentioning
confidence: 99%
“…For example, Easterling and Feldmeyer (2017) observed that women share a widespread feeling of shame and assume a new spoiled identity as a result of their incarceration. Women in prison are often viewed as doubly deviant or are twice stigmatized (Grundetjern 2018) for being both "bad mothers" and "bad women." This is also the case in Mexico (Montoya 2015).…”
Section: Motherhood In Prisonmentioning
confidence: 99%
“…This article aims to expand existing scholarship on how structurally disadvantaged mothers negotiate their maternal identities (for a review, see Grundetjern 2018) and to include the experiences of imprisoned women in the Global South. Latin American criminology has examined the experience of imprisoned women in general (Larroulet et al 2020;Lemgruber 1999;Salazar and Cabral 2012), but less research has been conducted on the experience of mothers in prison.…”
Section: Introductionmentioning
confidence: 99%